Lecturers’ Perception on the Adoption of Google Applications for Education (GAfE) in Nigeria - Falade, Ayotunde Atanda; Odewumi, Michael Olubunmi; Ogunlade, Oyeronke Olufunmilola; Aladesusi, Gboyega Ayodeji; Fagbenro, Modupeola Wuraola (Indonesian Journal of Curriculum and Educational Technology Studies, 2020)
Google Application for Education is a free suite of hosted communication and collaboration applications, provided by Google for educational institutions. This study investigates lecturers’ adoption of Google applications (apps) for education (GAFE) in university of Ilorin, Nigeria. The objectives of the study, among others, were to determine lecturers’ perceived adoption of Google Application for Education for instruction in a Nigerian university. The study adopted descriptive research design, using quantitative survey method. Four research questions and two hypotheses were answered and tested respectively. A total of one hundred and sixty-eight (168) respondents were randomly sampled; frequency counts, percentages and mean were employed to answer research questions while hypotheses were tested using t-test and analysis of variance (ANOVA). The findings of the study concluded, among many others, that lecturers perceived adoption and ease of adoption of GAFE for instruction in the university was positive. The study recommended that lecturers should be encouraged to explore full benefits of GAFE to improve classroom instruction. Abstrak Aplikasi Google untuk pendidikan (Google Applicaiton for Education, GAfE) merupakan aplikasi komunikasi dan kolaborasi yang disediakan oleh Google secara gratis untuk dunia pendidikan. Penelitian ini mengkaji adopsi GAfE oleh para dosen di Universitas Ilorin, Nigeria, terutama untuk mengetahui pemahaman para dosen dalam mengadopsi GAfE untuk perkuliahan. Penelitian ini mengadopsi desain deskriptif, terutama menggunakan survei. Terdapat empat pertanyaan penelitian yang diajukan dan dua hipotesis yang diuji. Sebanyak 168 responden dipilih secara acak, perhitungan frekuensi, persentase, dan rata-rata digunakan untuk menjawab pertanyaan penelitian, sementara hipotesis diuji menggunakan uji-t dan analisis varian (Anova). Penelitian ini merekomendasikan bahwa para dosen hendaknya harus didorong untuk mengeksplorasi manfaat sepenuhnya dari GAfE untuk meningkatkan kualitas pengajaran di kelas.